Women born with very low birth weight have similar menstrual cycle pattern, pregnancy rates and hormone profiles compared with women born at term - Gunilla Sydsjö; Pia Törnblom; P-O Gäddlin; Orvar Finnström; Ingemar Leijon; Nina Nelson; Elvar Theodorsson; Mats Hammar (BMC, 2019)
Abstract Background Individuals born very preterm or with very low birth weight (VLBW) have a reduced likelihood to reproduce according to population-based register studies. Extremely low-birth weight born adults had a lower reproduction rate for both men and women in a follow-up study. Aim To investigate if being born with VLBW is associated with differences in the reproductive health, i.e. age of menarche, menstrual cycle pattern, pregnancy rates and hormone profile compared with women born at term. Methods A prospective long-term follow-up of a cohort of live-born VLBW children and their controls studied repeatedly since birth and now assessed at 26-28 years of age. Of the totally 80 girls enrolled from birth 49 women (24 VLBW women and 25 controls) participated in the current follow-up. The women's anthropometric data and serum hormone levels were analysed. Results The reproductive hormone levels, including Anti-Mullerian Hormone, did not differ significantly between VLBW women and their controls. Both groups reported menstrual cycle irregularities and pregnancies to the same extent but the VLBW women reported 1.5 years later age of menarche. The VLBW subjects had a catch-up growth within 18 months of birth but remained on average 5 cm shorter in adult height. There were no significant differences in BMI, sagittal abdominal diameter, blood pressure or in their answers regarding life style between the VLBW women and the controls. Conclusion No differences in the reproductive hormone levels were found between VLBW women and their controls. Although age at menarche was somewhat higher in the VLBW group menstrual cycles and pregnancy rates were similar in the VLBW and control groups. Further follow-up studies are required to elucidate the health outcomes of being born VLBW.